NO
Searching Recurrent Set for Transition #1
Start location: l0
0: l0 -> l1 : x_2^0'=x_2^post0, x^0'=x^post0, x_1^0'=x_1^post0, x_3^0'=x_3^post0, x_4^0'=x_4^post0, (-x_2^0+x_2^post0 == 0 /\ x_3^post0-x_3^0 == 0 /\ -x^0+x^post0 == 0 /\ -x_1^0+x_1^post0 == 0 /\ -x_4^0+x_4^post0 == 0), cost: 1
1: l1 -> l1 : x_2^0'=x_2^post1, x^0'=x^post1, x_1^0'=x_1^post1, x_3^0'=x_3^post1, x_4^0'=x_4^post1, (2+2*x_1^0-x_3^0 > 0 /\ -x_2^0+x_2^post1 == 0 /\ x_1^post1-x_1^0 == 0 /\ 1-2*x_1^0+x_3^0 > 0 /\ x^post1-x^0 == 0 /\ -1+x_4^post1 == 0 /\ -1-2*x_2^0+x_3^0 == 0 /\ -1-2*x^0+x_3^0 == 0 /\ x_4^0 > 0 /\ 1-x_1^0+x_3^0 > 0 /\ -x_1^0+x_3^post1 == 0), cost: 1
Applied preprocessing
Original rule:
l1 -> l1 : x_2^0'=x_2^post1, x^0'=x^post1, x_1^0'=x_1^post1, x_3^0'=x_3^post1, x_4^0'=x_4^post1, (2+2*x_1^0-x_3^0 > 0 /\ -x_2^0+x_2^post1 == 0 /\ x_1^post1-x_1^0 == 0 /\ 1-2*x_1^0+x_3^0 > 0 /\ x^post1-x^0 == 0 /\ -1+x_4^post1 == 0 /\ -1-2*x_2^0+x_3^0 == 0 /\ -1-2*x^0+x_3^0 == 0 /\ x_4^0 > 0 /\ 1-x_1^0+x_3^0 > 0 /\ -x_1^0+x_3^post1 == 0), cost: 1
New rule:
l1 -> l1 : x_3^0'=x_1^0, x_4^0'=1, (2+2*x_1^0-x_3^0 > 0 /\ 1-2*x_1^0+x_3^0 > 0 /\ -1-2*x_2^0+x_3^0 == 0 /\ -1-2*x^0+x_3^0 == 0 /\ x_4^0 > 0 /\ 1-x_1^0+x_3^0 > 0), cost: 1
Found recurrent set
accelerating (1+2*x^0-x_3^0 >= 0 /\ 2+2*x_1^0-x_3^0 > 0 /\ 1-2*x_1^0+x_3^0 > 0 /\ -1-2*x_2^0+x_3^0 >= 0 /\ -1-2*x^0+x_3^0 >= 0 /\ x_4^0 > 0 /\ 1-x_1^0+x_3^0 > 0 /\ 1+2*x_2^0-x_3^0 >= 0) wrt. {x_3^0: x_1^0, x_4^0: 1}
1+2*x^0-x_3^0 >= 0 [0]: monotonic increase yields (1+2*x^0-x_3^0 >= 0 /\ 1-x_1^0+x_3^0 > 0), dependencies: 1-x_1^0+x_3^0 > 0
1+2*x^0-x_3^0 >= 0 [1]: eventual increase yields (1+2*x^0-x_3^0 >= 0 /\ x_1^0-x_3^0 <= 0)
2+2*x_1^0-x_3^0 > 0 [0]: monotonic increase yields (2+2*x_1^0-x_3^0 > 0 /\ 1-x_1^0+x_3^0 > 0), dependencies: 1-x_1^0+x_3^0 > 0
2+2*x_1^0-x_3^0 > 0 [1]: eventual increase yields (2+2*x_1^0-x_3^0 > 0 /\ x_1^0-x_3^0 <= 0)
1-2*x_1^0+x_3^0 > 0 [0]: eventual increase yields (1-2*x_1^0+x_3^0 > 0 /\ -x_1^0+x_3^0 <= 0)
-1-2*x_2^0+x_3^0 >= 0 [0]: eventual increase yields (-1-2*x_2^0+x_3^0 >= 0 /\ -x_1^0+x_3^0 <= 0)
-1-2*x^0+x_3^0 >= 0 [0]: eventual increase yields (-1-2*x^0+x_3^0 >= 0 /\ -x_1^0+x_3^0 <= 0)
x_4^0 > 0 [0]: monotonic increase yields x_4^0 > 0
1-x_1^0+x_3^0 > 0 [0]: monotonic increase yields 1-x_1^0+x_3^0 > 0
1+2*x_2^0-x_3^0 >= 0 [0]: monotonic increase yields (1-x_1^0+x_3^0 > 0 /\ 1+2*x_2^0-x_3^0 >= 0), dependencies: 1-x_1^0+x_3^0 > 0
1+2*x_2^0-x_3^0 >= 0 [1]: eventual increase yields (x_1^0-x_3^0 <= 0 /\ 1+2*x_2^0-x_3^0 >= 0)
solution:
1+2*x^0-x_3^0 >= 0: 1
2+2*x_1^0-x_3^0 > 0: 1
1-2*x_1^0+x_3^0 > 0: 0
-1-2*x_2^0+x_3^0 >= 0: 0
-1-2*x^0+x_3^0 >= 0: 0
x_4^0 > 0: 0
1-x_1^0+x_3^0 > 0: 0
1+2*x_2^0-x_3^0 >= 0: 1
resulting guard: (1+2*x^0-x_3^0 >= 0 /\ 2+2*x_1^0-x_3^0 > 0 /\ 1-2*x_1^0+x_3^0 > 0 /\ -1-2*x_2^0+x_3^0 >= 0 /\ x_1^0-x_3^0 <= 0 /\ -1-2*x^0+x_3^0 >= 0 /\ -x_1^0+x_3^0 <= 0 /\ x_4^0 > 0 /\ 1-x_1^0+x_3^0 > 0 /\ 1+2*x_2^0-x_3^0 >= 0)
resulting guard is a recurrent set